Human Resource Development Strategy in Cimahi Catering MSMEs Based on Maslow's Theory - Rais Apriyadi, Moh Taufik; Al Hadad, Alwi (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
Catering MSMEs in Cimahi play a vital role in the local economy but still face challenges in human resource (HR) management. This study aims to analyze HR development strategies in Cimahi’s catering MSMEs based on Abraham Maslow’s theory. A qualitative approach was used, involving interviews, observations, and documentation of three catering businesses: Katering Bu Ade, Katering Dapur Teh Nunung, and Katering Barokah. The findings show different HR management approaches depending on business scale. Katering Bu Ade focuses on fulfilling employees’ basic needs without structured training. Katering Dapur Teh Nunung has introduced incentive systems and teamwork to enhance motivation. Meanwhile, Katering Barokah applies a more comprehensive HR strategy, including continuous training, reward systems, and career development opportunities. Maslow’s hierarchy of needs suggests that motivation and productivity increase when employees’ needs are met at higher levels. Therefore, HR management strategies based on Maslow’s theory can effectively improve workforce performance. This study recommends enhancing HR capabilities through training, better incentive systems, and professional HR management to boost the competitiveness of catering MSMEs in Cimahi.